A Review on Failure Modes and Cracking Behaviors of Polypropylene Fibers Reinforced Concrete - Jawad Ahmad; Dumitru Doru Burduhos-Nergis; Mohamed Moafak Arbili; Saleh M. Alogla; Ali Majdi; Ahmed Farouk Deifalla (Buildings, 2022)
Despite being strong under compression, concrete is rather weak when subjected to tensile stress. Concrete has been reinforced with a variety of materials over time in order to resist tensile stresses. Among various types of fibers, polypropylene fiber, which is available in a range of sizes, is being used to strengthen concrete. The fiber also increases the concrete’s toughness, durability, and low permeability. Polypropylene fibers may be utilized in place of conventional reinforcement, according to a number of researchers. The aim of this study is to collect information from already carried out research on polypropylene fibers. Important characteristics of concrete, such as workability, compressive, tensile, and flexural strength, are reviewed. The review also explores cracking behavior and failure modes of polypropylene fiber reinforced concrete. Furthermore, durability aspects, such as water absorption, porosity, dry shrinkage, and microstructure study (scan electronic microscopy), were also reviewed. Results indicate that polypropylene fiber improved the mechanical strength and durability of concrete (particularly tensile capacity) but decreased the flowability of concrete. The optimum dose is important, as a higher dose adversely affects strength and durability due to a lack of flowability. Scanning electronic microscopy results indicate that the polypropylene fibers restrict the propagation of cracks, which improves the strength and durability of concrete. The review also indicates that shrinkage cracks are considerably reduced with the addition of polypropylene fibers. Finally, the review also provides future research guidelines for upcoming generations to further improve the performance of polypropylene fibers that reinforce concrete.